Applied genetics : recent trends and techniques - Emmanuel, C. (MJP Publishers, 2006)
Genetics is the science of heredity that involves the study of structure and function of genes. Applied genetics refers to the study of the involvement of the structure and function of genes in various practical fields. This book provides a focused introduction to the basic genetic principles and presents the molecular aspects and latest applied areas in genetics in considerable detail. The simple and lucid presentation of complicated topics in basic genetics, molecular genetics, medical genetics and in the latest applied areas of genetics would prove to be very useful to students, researchers and teachers.